TVET TEACHER TRAINING IN SOUTH AFRICA: LITERATURE REVIEW - Zascerinska, Jelena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
In the light of the annually increasing TVET learners’ enrolment numbers,TVET lecturers are central in TVET institutions. However, TVET teachers’ training in South Africa is under-explored.The research aim is to analyse literature on TVET teachers’ training in South Africa underpinning the elaboration of directions of further research. Literature review served as the research method was implemented in November-December 2021. The obtained data were structured in accordance with the previously established criteria. Summarising content analysis was performed. The conclusion is that the research done in the field of TVET lecturers’ training programmes in South Africa is fragmentedly presented to the scientific community. The structuring content analysis allows finding that the research in the field of TVET lecturers’ training programmes does not address TVET lecturers’ digital skills despite their impact on human being everyday life in the light of COVID-19 pandemic. Another finding is the entrepreneurship education is not embedded into TVET lecturers’ training programmes, too. Future work will include the implementation of empirical studies in the field of the analysis of TVET training programmes in South Africa. The novelty of the research is reflected in the directions of further work.